Pengaruh Suku Bunga terhadap Pertumbuhan Ekonomi: Sistematic Literature Review - Rizna Nur Rahmadhinta (Universitas 17 Agustus 1945 Jakarta, 2026)
This study aims to analyze the effect of interest rates on economic growth using a Systematic Literature Review (SLR) approach. Interest rates are a key instrument in monetary policy, playing a crucial role in maintaining economic stability and influencing investment and consumption activities. However, empirical findings show inconsistent results regarding the impact of interest rates on economic growth. Some studies suggest that low interest rates can stimulate economic growth by increasing investment and consumption, while others find that interest rates have no significant effect or may even exert a negative impact on growth. Moreover, interest rates are not always the primary determinant of economic growth and, under certain conditions, may be counterproductive. The review also indicates that the effect of interest rates does not operate in isolation but is influenced by other macroeconomic variables such as inflation, investment, and money supply. The relationship between interest rates and economic growth is also non-linear and dynamic, meaning that changes in interest rates do not produce uniform effects across different economic conditions. Additionally, interest rate volatility can create uncertainty, which may negatively affect economic growth. Therefore, the impact of interest rates on economic growth is contextual and highly dependent on overall macroeconomic conditions.